Metabolomic analyses of vigabatrin (VGB)-treated mice: GABA-transaminase inhibition significantly alters amino acid profiles in murine neural and non-neural tissues. (May 2019) - Walters, Dana C.; Arning, Erland; Bottiglieri, Teodoro; Jansen, Erwin E.W.; Salomons, Gajja S.; Brown, Madalyn N.; Schmidt, Michelle A.; Ainslie, Garrett R.; Roullet, Jean-Baptiste; Gibson, K. Michael
Abstract: The anticonvulsant vigabatrin (VGB; Sabril R ) irreversibly inhibits GABA transaminase to increase neural GABA, yet its mechanism of retinal toxicity remains unclear. VGB is suggested to alter several amino acids, including homocarnosine, β-alanine, ornithine, glycine, taurine, and 2-aminoadipic acid (AADA), the latter a homologue of glutamic acid. Here, we evaluate the effect of VGB on amino acid concentrations in mice, employing a continuous VGB infusion (subcutaneously implanted osmotic minipumps), dose-escalation paradigm (35–140 mg/kg/d, 12 days), and amino acid quantitation in eye, visual and prefrontal cortex, total brain, liver and plasma. We hypothesized that continuous VGB dosing would reveal numerous hitherto undescribed amino acid disturbances. Consistent amino acid elevations across tissues included GABA, β-alanine, carnosine, ornithine and AADA, as well as neuroactive aspartic and glutamic acids, serine and glycine. Maximal increase of AADA in eye occurred at 35 mg/kg/d (41 ± 2 nmol/g (n = 21, vehicle) to 60 ± 8.5 (n = 8)), and at 70 mg/kg/d for brain (97 ± 6 (n = 21) to 145 ± 6 (n = 6)), visual cortex (128 ± 6 to 215 ± 19) and prefrontal cortex (124 ± 11 to 200 ± 13; mean ± SEM; p < 0.05), the first demonstration of tissue AADA accumulation with VGB in mammal. VGB effects on basic amino acids, including guanidino-species, suggested the capacity of VGB to alter urea cycle function and nitrogen disposal. The known toxicity of AADA in retinal glial cells highlights new avenues for assessing VGB retinal toxicity and other off-target effects. Highlights: Continuous vigabatrin dosing induces amino acid alterations in mouse tissues. Altered neuroactive amino acids indicate imbalanced excitation/inhibition. 2-aminoadipate, a glial cell toxin, increases with VGB intake in surveyed tissues. Basic amino acid changes suggest disrupted urea cycle activity/nitrogen disposal. Ours is the first metabolomic analysis of VGB toxicity reported in the mouse.